2023
DOI: 10.1021/acs.orglett.3c01119
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Aldehyde–Palladium Catalysis Enables Asymmetric Synthesis of α-Alkyl Tryptophans via Cascade Heck-Alkylation Reaction

Abstract: The first catalytic asymmetric cascade Heck-alkylation reaction of NH 2 -unprotected amino acid esters with N-(2iodophenyl)allenamides is reported in this work. Under the promotion of a combining catalytic system comprising a chiral aldehyde, a chiral palladium complex, and the Lewis acid ZnCl 2 , the title reaction takes place smoothly, giving optically active α-alkyl tryptophan derivatives in moderate to good yields and excellent enantioselectivities. The target products can be converted into other structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In the same year, Guo and his research team reported the pioneering aldehyde-combining palladium co-catalyzed asymmetric cascade Heck-alkylation reaction between N-(2-Iodophenyl)allenamides 112 and NH 2 -unprotected amino acid esters 107 (as illustrated in Scheme 36). [95] The model reaction product 113 a was obtained in outstanding yields and enantioselectivities. Notably, chiral γ-lactam 113 b and chiral 1,2dihydroquinoline 113 d products were generated with good yields and excellent enantioselectivities.…”
Section: The Usage Of the Aldehyde/transition Metal Combining Catalyt...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the same year, Guo and his research team reported the pioneering aldehyde-combining palladium co-catalyzed asymmetric cascade Heck-alkylation reaction between N-(2-Iodophenyl)allenamides 112 and NH 2 -unprotected amino acid esters 107 (as illustrated in Scheme 36). [95] The model reaction product 113 a was obtained in outstanding yields and enantioselectivities. Notably, chiral γ-lactam 113 b and chiral 1,2dihydroquinoline 113 d products were generated with good yields and excellent enantioselectivities.…”
Section: The Usage Of the Aldehyde/transition Metal Combining Catalyt...mentioning
confidence: 99%
“…[80] In 2018, Yu and colleagues introduced two novel transient directing groups that exhibit selectivity towards γ-methylene and δ-methyl C(sp 3 )À H bonds, even in the presence of other reactive CÀ H bonds. They successfully achieved palladiumcatalyzed γ-methylene-C(sp 3 )À H heteroarylation and δ-C(sp 3 )À H arylation reactions using simple aliphatic amines (94) and iodoarenes (95) or aryl bromide (95') as coupling partners. These reactions relied on the cooperative combination of the newly developed transient directing groups C-26/C-28 and the ligand pyridine L1.…”
Section: The Usage Of the Aldehyde/transition Metal Combining Catalyt...mentioning
confidence: 99%
“…Under the promotion of a combined catalytic system comprising chiral aldehyde A2k , chiral palladium complex, and ZnCl 2 , the cascade Heck-alkylation reaction of amino acid esters with N -(2-iodophenyl)­allenamides 47 proceeded smoothly (Scheme ). The reaction was proposed to proceed via a palladium-catalyzed intramolecular addition of the C–I bond to allene, generating a π-allyl-palladium complex from 47 , followed by an enantioselective nucleophilic addition with the chiral aldehyde-activated amino acid esters to give the optically active α- quaternary tryptophans . Notably, chiral 1,2-dihydroquinoline 48g was also generated with the utilization of tert -butyl buta-2,3-dien-1-yl­(2-iodophenyl)­carbamate 47g as a reactant.…”
Section: Cooperative Catalysis Of Chiral Aldehydes and Transition Met...mentioning
confidence: 99%
“…Diverse nucleophiles were applied to undergo the subsequent allylic substitution reaction, offering different opportunities for the difunctionalization of allenamides. 7 Representatively, dicarbofunctionalization processes were reported by Sato's, 8 Lin's, 9 Guo's, 10 Hoarau's, 11 Guo's, 12 and other groups, 13 using different carbon nucleophiles. For example, in 2018, Hoarau and co-workers reported a palladium-catalysed construction of isoquinolone-azole bisheterocyclic scaffolds through a C–H allylation reaction (Scheme 1b).…”
mentioning
confidence: 99%